Therapeutic potential of robots for people who stutter: a preliminary study - Yoshikawa, Yuichiro; Kobayashi, Hiroaki; Sakai, Naomi; Ishiguro, Hiroshi; Kumazaki, Hirokazu (Frontiers in Psychiatry, 2024)
Introduction Growing anecdotal evidence suggests the feasibility of robotic intervention for people who suffer from disorders related to state anxiety. Few studies have been conducted on utilizing robots for persons who stutter (PWS). The present study examines the feasibility of using a robot for speech therapy for PWS. Methods We prepared four settings (i.e., interviews with unfamiliar persons, interviews with unfamiliar communication robots, reading sentences aloud with a tandem robot that can utter the same words as a user by repeating the user’s voice after a short delay, and reading sentences aloud while being alone). We assessed the potential of the robots as both interlocutors and practice partners in training with delayed auditory feedback (DAF) for PWS. Moreover, we assessed the relationship between the trait of stuttering and the participants’ affinity to the robots. Results Eleven PWS participated in the study. Eight (72.7%) participants had fewer stuttering-related psychological symptoms when they communicated with robots than when they communicated with humans. Spearman’s rank correlation analysis revealed that there was a significant negative correlation between the Modified Erickson Communication Attitude scale (S-24) and the difference between the scores for stuttering-related psychological symptoms pertaining to the communication robot and humans (p < 0.01). Six participants (54.5%) had fewer stuttering-related psychological symptoms when they read aloud with the tandem robot than when they read aloud alone. There were significant positive correlations between S-24 and the differences between the scores for stuttering-related psychological symptoms when reading aloud with the tandem robot and those when reading aloud alone (p < 0.01). Discussion The communication robot and tandem utterance robot can sometimes be burdensome, although both robots were always easier to talk to for PWS in this preliminary study. The participants with positive speech-related attitudes were more inclined to decrease stuttering-related psychological symptoms when communicating with CommU than when communicating with humans. The participants whose speech-related attitudes were negative were more inclined to show a decrease in stuttering-related psychological symptoms when reading aloud with the tandem robot. Further studies are needed to provide more detailed information.